New Zealand : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper discusses interactions between external risks and the New Zealand economy. The current set of external risks has the potential to be extremely damaging to New Zealand, but two factors would likely mitigate the economic impact. First, the flexible exchange rate regime is a reliable shock absorber and automatic stabilizer from the perspective of GDP, although it leads to a rebalancing between the domestic and external sectors in the economy. Second, net migration flows can reduce the negative impact of lower external demand under some circumstances, such as a growth slowdown in Australia. Fiscal policy could also offset some of the short-term costs of adjustment. Fiscal policy can provide stimulus at relatively small and manageable cost to the already-low government debt to GDP ratio. Moreover, at the current juncture, fiscal policy might need to provide the bulk of policy support against negative shocks, as monetary policy might be ineffective if has become constrained by an effective lower bound on the monetary policy interest rate.